Digital-based Plastic Waste Collection System in the Context of Sustainable Development Goals - Herdiansyah, Herdis; Gustiawati, Beatriks Liku; Frimawaty, Evi (Department of Urban and Regional Planning, Diponegoro University, 2025)
An effective waste collection system is an essential step in plastic waste handling and impacts positively on recycling rates. In the era of digital technology transformation, digital-based plastic waste collection and recycling have emerged to offer innovative solutions for more effective plastic waste management from upstream to downstream which contribute to the Sustainable Development Goals target. However, this solution has not been widely implemented in Indonesia. Therefore, this study aims to synthesize the role of digitalization of waste collection in accomplishing the Sustainable Development Goals. This study employed with a qualitative approach through semi-structured interviews. Bibliometric analysis using VOSviewer version 1.6.20 was conducted to map prior studies on the digitalization of waste collection in the context of achieving the Sustainable Development Goals. This study confirms that the digitalization of waste collection contributes to the achievement of the three pillars of the Sustainable Development Goals, example economics, social, and environmental pillar.